Secret sharing-based authentication and key agreement protocol for machine-type communications - Ana Paula G Lopes; Lucas O Hilgert; Paulo RL Gondim; Jaime Lloret (International Journal of Distributed Sensor Networks)
One of the main challenges for the development of the Internet of Things is the authentication of large numbers of devices/sensors, commonly served by massive machine-type communications, which jointly with long-term evolution has been considered one of the main foundations for the continued growth of Internet of Things connectivity and an important issue to be treated in the development of 5G networks. This article describes some protocols for the group-based authentication of devices/sensors in Internet of Things and presents a new group authentication protocol based on Shamir’s secret and Lagrange interpolation formula. The new protocol protects privacy, avoids unauthorized access to information, and assists in the prevention of attacks, as replay, distributed denial of service, and man-in-the-middle. A security analysis and comparisons among the 3GPP evolved packet system authentication and key agreement standard protocol and other recent group authentication protocols were performed toward proving the efficiency of the proposed protocol. The comparisons regard security properties and computational and communication costs. The safety of the protocol was formally verified through simulations conducted by automated validation of internet security protocols and applications.